Effects of Lithium Incorporation on the Morphological, Optical, and Sensing Properties of ZnO Thin Films Synthesized By Chemical Spray Pyrolysis - Dawood M. Khudhair; Alyaa A. Abd-Aljbar; Sami Salman Chiad (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research explores the effect of lithium (Li) doping on the structural, morphological, optical, and gas-sensing characteristics of zinc oxide (ZnO) thin films, which were deposited onto glass substrates using the chemical spray pyrolysis technique. X-ray diffraction (XRD) analysis revealed that all the films are polycrystalline in nature with a hexagonal wurtzite structure, exhibiting a preferred orientation along the (100) plane. Li incorporation induced a shift in diffraction peaks and significantly influenced microstructural parameters; the crystallite size increased to a maximum of 23.34 nm for the 4% Li-doped film, while dislocation density and microstrain decreased, indicating improved crystallinity. Atomic force microscopy (AFM) analysis showed that Li doping leads to a more uniform and compact surface morphology, accompanied by a reduction in both average particle size and surface roughness. Optical analysis revealed that Li doping induced a red shift in the absorption edge and reduced the optical band gap from 3.38 eV in pure ZnO to 3.25 eV in the 4% Li-doped film, an effect attributed to the introduction of defect states within the band gap. Furthermore, the gas sensing response to nitrogen dioxide (NO₂) was evaluated, with the highest doped film showing the lowest response, Li doping serves as an effective approach for tailoring the physical properties of ZnO.